Striped Blister Beetle, Epicauta vittata (Fabricius) (Coleoptera: Meloidae) - John L. Capinera (EDIS, 2004)
The striped blister beetle, Epicauta vittata (Fabricius), is a native species. It has been collected from all eastern states west to, and including, South Dakota, Nebraska, Kansas and Oklahoma. In Canada it is known from Quebec and Ontario. Populations from the southeastern coastal plain including Florida, southern Georgia and eastern South Carolina differ in appearance from beetles found elsewhere and are called the 'lemniscate race,' but interbreed successfully with normal beetles. This document is EENY-280, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2003.